2022
DOI: 10.3390/cancers15010264
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy as a Promising Option for the Treatment of Advanced Chordoma: A Systemic Review

Abstract: Objective: To summarize the function and efficacy of immunotherapy as an adjunctive therapy in the treatment of advanced chordoma. Methods: Literature search was conducted by two reviewers independently. Case reports, case series and clinical trials of immunotherapy for chordoma were retrieved systematically from Pubmed, Web of Science, Scoupus and Cochrane Library. Clinical outcome data extracted from the literature included median progression-free survival (PFS), median overall survival (OS), clinical respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Current FDA approved PD-L1 inhibitors include avelumab, durvalumab, and atezolizumab for specific uses in advanced urothelial carcinoma, renal cell carcinoma, and non-small cell lung cancer (NSCLC), among others ( 46 ). Although pembrolizumab and nivolumab (PD-1 inhibitors) have been the more commonly studied immune checkpoint inhibitors in chordoma, durvalumab and FAZ053 (monoclonal antibodies with PD-L1 targets) were applied to limited chordoma treatment regimens with some clinical benefit ( 47 , 48 ). To date, few ongoing clinical trials for PD-1/PD-L1 inhibitors include chordoma patients (NCT02936102, NCT02834013, NCT03190174).…”
Section: Discussionmentioning
confidence: 99%
“…Current FDA approved PD-L1 inhibitors include avelumab, durvalumab, and atezolizumab for specific uses in advanced urothelial carcinoma, renal cell carcinoma, and non-small cell lung cancer (NSCLC), among others ( 46 ). Although pembrolizumab and nivolumab (PD-1 inhibitors) have been the more commonly studied immune checkpoint inhibitors in chordoma, durvalumab and FAZ053 (monoclonal antibodies with PD-L1 targets) were applied to limited chordoma treatment regimens with some clinical benefit ( 47 , 48 ). To date, few ongoing clinical trials for PD-1/PD-L1 inhibitors include chordoma patients (NCT02936102, NCT02834013, NCT03190174).…”
Section: Discussionmentioning
confidence: 99%
“…Besides a potential prognostic value, the observed biological difference between two chordoma subtypes with potentially important clinical implications in terms of the therapy. Immunotherapy, that include the use of immune checkpoint inhibitors (ICI) is a promising therapeutic avenue in chordoma and number of clinical trials on this field has been already initiated [ 58 ]. Importantly, the level of tumor-infiltrating lymphocytes is generally one of most relevant indicators of response to this therapy [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the above encouraging results, a Phase II clinical study on PD-L1 monoclonal antibody combined with CTLA-4 monoclonal antibody for advanced or metastatic bone tumors showed that among the 5 chordoma patients included in the study, only 1 patient had obvious tumor shrinkage and achieved CR after receiving a full course of twelve cycles (53). Xiang et al conducted a systematic review of 22 chordoma cases involving progression from 2015 to 2022 and found that combination therapy with PD-1/PD-L1 antibodies and CTLA-4 monoclonal antibody was no more effective than monotherapy with PD-1/PD-L1 antibodies, but it was more toxic (54). However, due to the small number of cases and inconsistent drug regimens, the reliability of this result needed to be further verified.…”
Section: Ici Therapymentioning
confidence: 99%